Thales of Miletus and philosophical application of mathematics (IF-Sophia: revista eletrônica de investigações Filosófica, Científica e Tecnológica, 2016)
This paper aims to introduce the reader to the thought of Thales of Miletus about what the future would be called "Philosophy" and their interactions toward mathematical thinking. In this regard, the objective is to present the experience of field-empirical mathematician Thales, in Ionia and Egypt and the Near East, for the anthropological and cultural exchanges that took place in order to equip the Ionian thinker resources capable of promoting his fame as one of the seven Sages of Greece, but above all, his pedagogical innovation, and mathematicians made inherent in the exercise of Hellenic wisdom in preparation. Finally, the paper aims to highlight the process of interaction between mathematics and revisionist critical rationalism that was to develop a new view of the social character of Truth Master and certainly would mark the next step as Philosophy and consequent to mathematical knowledge.
Keywords: Array; Array; Array; Array; Array